2003
DOI: 10.1086/377540
|View full text |Cite
|
Sign up to set email alerts
|

Outcome ofStaphylococcus aureusBacteremia in Patients with Eradicable Foci versus Noneradicable Foci

Abstract: To determine the outcome of Staphylococcus aureus bacteremia (SAB) on mortality, including the impact of methicillin resistance and an initial delay (< or =48 h) of appropriate antibiotics, a retrospective cohort study including 238 patients with SAB was performed. By logistic regression, noneradicable or noneradicated foci, underlying cirrhosis, and cancer were found to be independent predictors of mortality. In patients with eradicable foci, there were no significant differences in the associated mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 16 publications
4
92
1
4
Order By: Relevance
“…aureus causes a wide spectrum of diseases ranging from mild to life-threatening (25,27). Disease severity is determined by organism-related virulence factors and host condition (15,18,21,37). S. aureus virulence factors are numerous and include surface proteins and toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus causes a wide spectrum of diseases ranging from mild to life-threatening (25,27). Disease severity is determined by organism-related virulence factors and host condition (15,18,21,37). S. aureus virulence factors are numerous and include surface proteins and toxins.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome is usually determined by virulence factors and host response (15,16,18,21,24,36). Many virulence factors have been implicated in invasiveness, disease severity, and persistent bacteremia (1,8,10,11,12,24,30,36).…”
mentioning
confidence: 99%
“…An indication as to which patient subgroups would benefit emerged from a study by Lodise et al, who observed that the greatest impact of empirical antibiotics (within 44.75 h) occurred in patients with severe disease (APACHE II score of Ͼ15.5) or complicated SAB (176). However, a larger single-center study of 814 SAB episodes detected a reduced mortality rate only for empirically (24 h before to 24 h after the index blood culture) treated patients with the lowest severity-of-illness score (modified APACHE III score) (HR, 2.42; 95% CI, 1.7 to 3.44) (257), whereas a study by Kim et al noted that empirical antibiotics (within 48 h) resulted in outcome differences only for patients with a noneradicable focus compared to eradicable foci of SAB (142). Conversely, some patients will improve irrespective of inadequate empirical or definitive SAB therapy (6).…”
Section: Empirical Antibiotics/antibiotic Timingmentioning
confidence: 99%
“…En los diversos estudios realizados se han identificado múltiples factores relacionados con aumento de la morbimortalidad, asociada con la bacteriemia por S. aureus (12,15,17,18,30,54,55). Se han identificado factores del huésped que se asocian con un desenlace adverso, como edad mayor de 60 años e inicio de la bacteriemia en la comunidad (56)(57)(58)(59)(60).…”
Section: Factores De Riesgo Y Pronósticosunclassified
“…En los Estados Unidos, entre 1980 y 1990, se incrementaron los casos de bacteriemia por S. aureus en 283% en hospitales no universitarios y, en 176%, en hospitales universitarios (7,12,13). Según el lugar de adquisición de la bacteriemia por S. aureus se encuentra que 17% a 49% se originan en la comunidad, 51% a 83% son hospitalarias y 30% a 38% están asociadas con trabajadores de la salud (ver más adelante) (13)(14)(15)(16)(17).…”
unclassified